Respuesta :

Answer:

-2,-9

5,12

Step-by-step explanation:

Set the equations equal to each other

x^2 - 13 = 3x - 3

x^2 - 10 = 3x

x^2 - 3x - 10 = 0

(x-5)(x+2) = 0

x = 5 x = -2

Now choose on the equations to plug into

y = 3x - 3

y = 3(-2) - 3 = -9

y = 3(5) - 3 = 12

-2,-9

5,12

Answer:

[tex](x,y)=\left(\; \boxed{-2,-9} \; \right)\quad \textsf{(smaller $x$-value)}[/tex]

[tex](x,y)=\left(\; \boxed{5,12} \; \right)\quad \textsf{(larger $x$-value)}[/tex]

Step-by-step explanation:

Given system of equations:

[tex]\begin{cases}y=x^2-13\\y=3x-3\end{cases}[/tex]

To solve by the method of substitution, substitute the first equation into the second equation and rearrange so that the equation equals zero:

[tex]\begin{aligned}x^2-13&=3x-3\\x^2-3x-13&=-3\\x^2-3x-10&=0\end{aligned}[/tex]

Factor the quadratic:

[tex]\begin{aligned}x^2-3x-10&=0\\x^2-5x+2x-10&=0\\x(x-5)+2(x-5)&=0\\(x+2)(x-5)&=0\end{aligned}[/tex]

Apply the zero-product property and solve for x:

[tex]\implies x+2=0 \implies x=-2[/tex]

[tex]\implies x-5=0 \implies x=5[/tex]

Substitute the found values of x into the second equation and solve for y:

[tex]\begin{aligned}x=-2 \implies y&=3(-2)-3\\y&=-6-3\\y&=-9\end{aligned}[/tex]

[tex]\begin{aligned}x=5 \implies y&=3(5)-3\\y&=15-3\\y&=12\end{aligned}[/tex]

Therefore, the solutions are:

[tex](x,y)=\left(\; \boxed{-2,-9} \; \right)\quad \textsf{(smaller $x$-value)}[/tex]

[tex](x,y)=\left(\; \boxed{5,12} \; \right)\quad \textsf{(larger $x$-value)}[/tex]

ACCESS MORE